2017
DOI: 10.12998/wjcc.v5.i4.153
|View full text |Cite
|
Sign up to set email alerts
|

Ominous lung cavity “Tambourine sign”

Abstract: Mucinous adenocarcinoma represents a rare subtype of adenocarcinoma of the lung, which is frequently invasive and has a poorer prognosis. Of its wide range of imaging appearances, air-space consolidation is the most frequent pattern while cavitary form has only rarely been reported. Despite imaging advancements, the differentiation of benign and malignant cavitary lung lesions sometimes remains imperfect. We propose “Tambourine” sign on computed tomography to raise the suspicion of mucinous adenocarcinoma in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…One such report had similar CT evidence of patchy airspace consolidations with cavitations and was also initially thought to be infectious in origin and treated with antibiotic therapy [ 8 ]. CT imaging in two other cases revealed multiple cavitary lesions similar to our present case [ 9 , 10 ]. Another report described CT findings of a single cavitary lesion, later pathologically confirmed as adenocarcinoma [ 11 ].…”
Section: Discussionsupporting
confidence: 84%
“…One such report had similar CT evidence of patchy airspace consolidations with cavitations and was also initially thought to be infectious in origin and treated with antibiotic therapy [ 8 ]. CT imaging in two other cases revealed multiple cavitary lesions similar to our present case [ 9 , 10 ]. Another report described CT findings of a single cavitary lesion, later pathologically confirmed as adenocarcinoma [ 11 ].…”
Section: Discussionsupporting
confidence: 84%
“…Multiple cavitary lesions in the lung can be observed in many diseases such as tuberculosis, nontuberculous mycobacterial infection, and primary or metastatic lung cancer [ 8 ]. To the best of our knowledge, there are a few case reports of IMAs with cavities [ 2 , 3 ]. It has been reported that 7-13% of IMAs are accompanied by a cavity, and cavitary IMA tends to have a poor prognosis compared with noncavitary IMA [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Invasive mucinous adenocarcinoma (IMA), formerly classified as mucinous bronchioloalveolar carcinoma, is a variant of adenocarcinoma according to the International Association for the Study of Lung Cancer/American Thoracic Society/European Respiratory Society lung adenocarcinoma classification system [ 1 ]. The typical computed tomography (CT) finding of IMA is multiple consolidations or ground-glass opacities mimicking pneumonia; however, there are a few reports of IMA with cavitary lesions [ 2 , 3 ]. Here, we report a case of IMA with multiple lung cavities.…”
Section: Introductionmentioning
confidence: 99%
“…We report a case of IMA with confluent cavitary lesions in the lung following the guidelines of the CARE guide for case reports [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%